Germinação e crescimento de plântulas de Enterolobium contorsiliquum (Vell.) Morong em função do peso de semente, localização no fruto e condições de temperatura e luz. - Lessa, Bruno França da Trindade (2013)
Currently comes increasing the interest with agronomical emphasis by native forest species from Brazil, due its applications in various sectors of the economy. The “tamboril” (Enterolobium contorsiliquum (Vell.) Morong) is one of these species, presenting importance for the timber, landscape, medical, beekeeping sector, beyond to be indicated for recovery of degraded large areas. The objective of this work was studying the seeds germination and seedlings growth of E. contorsiliquum in function of seeds weight, location on fruit and conditions of temperature and light. Two experiments were conducted: in the first, the seeds were separated according to the weight, in three classes (light, intermediaries and heavy), submitting each class to germination test under absence and presence of light in four different temperatures (20, 30, 40 and 20-30°C). This experiment was disposed in triple factorial squeme 3x2x4 (related to three classes, two light regimes and four temperatures) under completely randomized design, with four replications. In the second, the seeds were separated according to their location in the fruit (proximal, central and distal regions) and submitted to germination test under the temperatures of 25 and 20-30°C, using factorial squeme 3x2 (three locations and two temperatures) in completely randomized design with four replications. For both experiments were determined the variables: germination first count, final percentage and rate, length and dry weight of shoot, root and total, beyond of accelerated aging only for the second experiment. All data were submitted to normality test and, when they were presented normal was performed variance analysis and the compare means by Tukey test, when no normal only Mann-Whitney test. The germination of “tamboril” was shown to be insensitive to light with high percentage and rate when using the temperature of 40°C, however this temperature detracted the seedlings development. So the temperature more indicated for the settlement of “tamboril” is 30°C. The heavy seeds had always the best results, showing the use of these seeds ensures seedlings production more uniform and with good development. Among the variables assessed the location of the seeds influenced only the germination rate, which was higher for seeds of the distal region of the fruit at 25°C. Conclude also the alternating temperature doesn’t affect the seeds germination and seedlings growth of “tamboril”.